Penerapan Media 3D Sektchup Pada Ruang Kantor Kepala Sekolah SMK N 1 Pagaran - Simanjuntak, Daniel L; Lubis, Diana Suksesiwaty (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
This research aims to apply the sketchup application to design the principal's office building at SMK NEGERI 1 PAGARAN. The use of this sketchup application will make it easier for everyone who is in any field to turn an object or image into a 3D design and make it easier for the manager or employees or students majoring in TKJ at SMK N 1 PAGARAN to keep improving the building design. the method used in this research is descriptive qualitative. The design of the principal's office building is made by applying the sketchup software application. The results of the research have been successfully implemented so that it is expected to be able to help the manager of SMK N 1 PAGARAN in creating a better building for the future.